PENGARUH MEDIA KAMPANYE SARAPAN SEHAT TERHADAP PERUBAHAN PENGETAHUAN, SIKAP, DAN KEBIASAAN SARAPAN ANAK SEKOLAH DASAR DI KABUPATEN BOGOR - Dodik Briawan; Ikeu Ekayanti; Ratu Diah Koerniawati (Food and Nutrition Society of Indonesia, 2013)
The purpose of this study was to analyze the effect of a healthy breakfast campaign on the changes in knowledge, attitudes, and breakfast habits among elementary school children in Bogor District. A quasy experimental study was applied to this study. Subjects in this study were 229 elementary school children in the nine villages in Bogor District. Nutrition education media used in this study were power point, puppets, picture cards, and drama. The school childrens knowledge and attitude showed that there was a significant difference between media intervention of power point, puppet, and drama to picture cards. The highest scores of knowledge (73.23±1.14) and attitude (91.84±1.09) was in picture cards. The percentage of subjects having a habit of breakfast before intervention was 78.2% and increased to 81.7% after intervention. Media intervention by picture cards gave highest change to increased breakfast knowledge, attitude, and habits for elementary school children.